Design of Fixture for Rotor Post - Anbazhagan, R; Kalidoss, R; Suresh, R; Refugene James Dev, S; S, Srikanth; Raj M.G, Yeshwanth (International Journal of Engineering and Technology, 2018)
This paper deals with Design of Fixture for Rotor Post. The existing method is studied regarding the assembly of the rotor post using the normal marking. So, it is to suggest a design for the fixture for rotor post. It includes fixture plate design with leveled bed. The leveled bed is placed on the locator, providing the dimensioned fixture plate fixed on the leveled bed. The fixture plates are designed according to the size of the rotor post. The rotor post is placed on the leveled bed, the verticality of rotor post as in assembly is maintained. The committee has also interacted with shop executives about the work with additional safety also. This paper helps to improve the accuracy and increase the productivity of the rotor post. It also reduces the total time of the fabrication. Due to this work, the fabrication cost of the rotor post reduced.Â Â